Management of Financial Resources of Insurance Companies - kizi, Tugizova Malika Sohib (Research Parks Publishers, 2023)
In modern conditions of economic development, insurance is becoming one of the most dynamic branches of economic activity, which contributes to the protection of the property interests of enterprises and citizens, the security and stability of business. The role of insurance is especially important in the context of the ongoing economic reforms in Uzbekistan, since the availability of insurance coverage stimulates the development of market relations and business activity, improves the investment climate in the country. The economic efficiency of an insurance organization depends, first of all, on the management of financial flows and on the work to minimize the risks that threaten the company's activities.